Prenatal phthalate exposure and neurodevelopmental differences in twins at 2 years of age - Han Xiao; Liqin Hu; Tingting Tang; Jufang Zhong; Qiao Xu; Xiaonan Cai; Feiyan Xiang; Pan Yang; Hong Mei; Aifen Zhou (BMC, 2024)
Abstract Background Previous studies of singletons evaluating prenatal phthalate exposure and early neurodevelopment reported mixed results and the associations could be biased by parental, obstetrical, and genetic factors. Methods A co-twin control design was employed to test whether prenatal phthalate exposure was associated with children's neurocognitive development. We collected information from 97 mother-twin pairs enrolled in the Wuhan Twin Birth Cohort between March 2016 and October 2018. Fourteen phthalate metabolites were measured in maternal urine collected at each trimester. Neurodevelopmental differences in twins at the age of two were examined as the outcome of interest. Multiple informant model was used to examine the covariate-adjusted associations of prenatal phthalate exposure with mental development index (MDI) and psychomotor development index (PDI) scores assessed at 2 years of age based on Bayley Scales of Infant Development (Second Edition). This model also helps to identify the exposure window of susceptibility. Results Maternal urinary levels of mono-2-ethyl-5-oxohexyl phthalate (MEOHP) (β = 1.91, 95% CI: 0.43, 3.39), mono (2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) (β = 1.56, 95% CI: 0.33, 2.79), and the sum of di-(2-ethylhexyl) phthalate metabolites (∑DEHP) (β = 1.85, 95% CI: 0.39, 3.31) during the first trimester showed the strongest and significant positive associations with intra-twin MDI difference. When stratified with twin chorionicity, the positive associations of monoethyl phthalate (MEP), monoisobutyl phthalate (MiBP), mono-n-butyl phthalate (MBP), monobenzyl phthalate (MBzP), individual DEHP metabolites, and ∑DEHP exposure during pregnancy with intra-twin neurodevelopmental differences were more significant in monochorionic diamniotic (MCDA) twins than those in dichorionic diamniotic (DCDA) twins. Conclusions Neurodevelopmental differences in MCDA twins were strongly associated with prenatal phthalate exposure. Our findings warrant further confirmation in longitudinal studies with larger sample sizes.